Mindfulness in Elderly Care Services at Nursing Homes in Salatiga City - Suwartiningsih, Sri; Setiawan, Adi; Indah, Christina Maya; Sulistyaningsih, Endang; Hartiningsih, Tri (Global Writing Academica Researching & Publishing, 2024)
In the city of Salatiga, there are five nursing homes: Merbabu Nursing Home, Salib Putih Nursing Home, Menara Berkat Senior Residence, Maria Martha Senior Residence, and Menara Kasih. Each nursing home has a leader and staff who serve in their respective facilities. Most caregivers in these five nursing homes are women, with 59 female caregivers and only 32 male caregivers. The caregivers have the primary responsibility of serving the elderly residents in nursing homes. Some of these elderly residents are bedridden and require care in their beds, while others are blind, unable to walk, deaf, and so on. Given the nature of the caregivers' duties, it is essential to conduct research on the sense of calling among caregivers in nursing homes. Using a descriptive constructive method, the research aims to uncover facts that can build the concept of mindfulness in elderly care services at the nursing homes in Salatiga. The research findings reveal that the concept of mindfulness is shaped by the presence of meaning and values in the sense of calling, morality, responsibility, sincerity, and spirituality. The meaning and values within this calling include the opportunity to serve others, especially the elderly; the moral drive to joyfully serve the elderly; the responsibility toward others and the families of the elderly; sincerity in providing wholehearted care for the elderly; and spirituality, which sees serving the elderly as an act of faith in God.